Bayesian smoothing and regression for longitudinal, spatial and event history data - Fahrmeir, L.; Kneib, Thomas (Oxford : Oxford University Press, 2011)
Bringing together recent advances in smoothing and semiparametric regression from a Bayesian perspective, this book demonstrates, with worked examples, the application of these statistical methods to a variety of fields including forestry development economics, medicine and marketing.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Regression analysis; Bayesian statistical decision theory; Smoothing (Statistics)